Investigation of the potassium fluoride post deposition treatment on the CIGSe/CdS interface using hard X-ray photoemission spectroscopy – a comparative study. Issue 20 (10th May 2016) - Ümsür, Bünyamin; Calvet, Wolfram; Steigert, Alexander; Lauermann, Iver; Gorgoi, Mihaela; Prietzel, Karsten; Greiner, Dieter; Kaufmann, Christian A.; Unold, Thomas; Lux-Steiner, Martha Ch.
Abstract : Modifications at the CIGSe/CdS interface due to KF-PDT are studied using synchrotron radiation. Abstract : The impact of the potassium fluoride post deposition treatment on CIGSe chalcopyrite absorbers is investigated by means of depth resolved hard X-ray photoemission spectroscopy of the near surface region. Two similar, slightly Cu-poor CIGSe absorbers were used with one being treated by potassium fluoride prior to the chemical bath deposition of an ultrathin CdS layer. The thickness of the CdS layer was chosen to be in the range of about 10 nm in order to allow the investigation of the CIGSe/CdS interface by the application of hard X-rays, increasing the information depth up to 30 nm. Besides strong intermixing on both samples, an increased Cu depletion of the KF treated absorber was observed in combination with an increased accumulation of Cd and S. In addition, a general shift of about 0.15 eV to higher binding energies of the CIGSe valence band at the absorber surface as well as the CIGSe and CdS related core levels was measured on the KF treated sample. This phenomenon is attributed to the impact of additional cadmium which acts as donor and releases further electrons into the conduction band of the absorber. Finally, the electrons accumulate at the CdS surface after having passed the interface region. This additional surface charge leads to a pronounced shift in the photoemission spectra as observed on the KF treated CIGSe absorber compared to the non-treated absorber.